Bulk Transmissions for S-ALOHA Systems - Hu, Yangqian; Seo, Jun-Bae; Jin, Hu (IEEE Vehicular Technology Conference, 2022)
This work considers a bulk transmission scheme for slotted ALOHA (S-ALOHA) systems with a finite population of unsaturated terminals. In the system, once a user makes a successful random access (RA) via S-ALOHA, it can transmit C packets to the traffic channel. We examine an effective capacity, which is defined as the maximally admissible mean arrival rate to the system, subject to the constraint that each user's queue does not overflow. To obtain this capacity, we use the large deviation theory on the user's queueing process. For comparison, we also use the dominant pole method in order to obtain the butter overflow probability. We then show that results from the method of using the large deviation theory are asymptotically identical to those from the dominant pole method due to the same decaying rate, and that keeping the traffic load within the effective capacity prevents a user's queue from overflowing in practice.